Spontaneous Rupture of Fibrolamellar Variant Hepatocellular Carcinoma - Polavarapu, Abhishek D. (Gastroenterology Res, 2019)
Fibrolamellar hepatocellular carcinoma (FL-HCC) is a unique variant of hepatocellular carcinoma. The majority of cases present with nonspecific symptoms like vague abdominal pain, weight loss and fatigue. Ruptured FL-HCC occurs rarely and mortality in the acute phase is very high. We report a rare case of a ruptured FL-HCC successfully managed with transarterial embolization for hemostasis. A 37-year-old male previously in good health presented with a severe, sharp epigastric pain that started 1 h prior to the presentation. He denied trauma, fever, nausea, vomiting, or diarrhea. Tenderness in the epigastrium was noted, with no palpable masses, guarding or rigidity. His blood pressure and pulse were 159/105 mm Hg and 105 beats/min. Platelets and coagulation parameters were within normal limits; transaminases were elevated. Abdominal computed tomography (CT) scan with contrast revealed an 8 cm lobulated mass with central hypodensity in the left hepatic lobe with perilesional blood and free pelvic fluid, indicating tumor rupture. CT angiography showed tumor neovascularization from a branch of the left hepatic artery which was embolized using transarterial gelfoam. Liver magnetic resonance imaging (MRI) and biopsy were consistent with fibrolamellar variant hepatocellular carcinoma. After 4 days, as the symptoms resolved, and the lab results were stable, patient was discharged and underwent a left hepatectomy 3 weeks later. FL-HCC occurs commonly in the left lobe of a young and non-cirrhotic liver. Typically, cross sectional imaging reveals a lobulated mass with well-defined margins, areas of hypervascularity and a central calcified scar. Histologic appearance is characterized by eosinophilic polygonal shaped cells separated by lamellar fibrosis. Surgical resection is the treatment of choice with better outcome when compared to conventional HCC. Disease recurrence after complete surgical resection is however high in the first 5 years. Tumors > 5 cm in size are at high risk for rupture with high mortality and recurrence rates secondary to significant spillage of tumor. While an emergency hepatectomy is preferred in unstable patients, those that are hemodynamically stable can undergo radiologic transarterial embolization for hemostasis followed by staged hepatectomy.